If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 50 + -2x = 8 + -7x Solving 50 + -2x = 8 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 50 + -2x + 7x = 8 + -7x + 7x Combine like terms: -2x + 7x = 5x 50 + 5x = 8 + -7x + 7x Combine like terms: -7x + 7x = 0 50 + 5x = 8 + 0 50 + 5x = 8 Add '-50' to each side of the equation. 50 + -50 + 5x = 8 + -50 Combine like terms: 50 + -50 = 0 0 + 5x = 8 + -50 5x = 8 + -50 Combine like terms: 8 + -50 = -42 5x = -42 Divide each side by '5'. x = -8.4 Simplifying x = -8.4
| log^36(x)=0.5 | | -4(2-y)+3=3(y-4) | | (7y-3xz)squared= | | (9x+12)(2x-20)-64x=(3x-45)(6x-50)-90 | | xd=2x+7 | | 4(2x-3)4x= | | 18x^3+18x^2+4x-28=0 | | 155+60+x=180 | | 30+20+x=180 | | 102+137+x=180 | | 5x+2+8x+4+15x-19=180 | | 50+62+80+53+x=180 | | d=2(rv+rc+fc) | | 122+90+x=180 | | 6x+55=6x-40 | | 24x+12=11 | | z^2-2z+1-2i=0 | | d-23/3=-5 | | x^2-xy+3y^2=6 | | 18x^3+45x^2+37x+10=0 | | 9c-46=4c-9 | | -6+17r=24 | | 15c=8c+7 | | (6x+5)(3x+2)(x+1)=28 | | a*4+b*7=60 | | A=(4m+h) | | a=(am+h) | | 5=-6+a | | 14.6=10.2 | | -8=2+k | | -a+9-6a=12-7a-3 | | 5x-10+9x+18=2x+2+2x-2 |